2011
DOI: 10.1111/j.1600-0404.2011.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with lobar vs. non-lobar intracerebral hemorrhage

Abstract: Alongside risk factors conventionally thought to be related to LH, underweight may also be a LH-related factor, specifically in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…In this regard, our findings confirm and extend those of recent case-control analyses that pointed toward a negligible effect of obesity on the risk of cerebral amyloid angiopathy-related ICHs, as opposed to an independent influence on those related to hypertensive vasculopathy. 11,12 Actually, although we were not able to detect any significant independent contribution of obesity on the risk of deep ICH, we observed a significant IE as a result of the relationships between obesity and its comorbidities. Taken together with previous reports, our data suggest a complex relationship between obesity and cerebral hemorrhage, with different contributions of obesity-related conditions and, indirectly, support the prevailing idea that metabolic factors play a much larger role in the pathogenesis of deep ICH than in cerebral amyloid angiopathy-related hemorrhages.…”
Section: In the Context Of The Current Literaturecontrasting
confidence: 43%
See 1 more Smart Citation
“…In this regard, our findings confirm and extend those of recent case-control analyses that pointed toward a negligible effect of obesity on the risk of cerebral amyloid angiopathy-related ICHs, as opposed to an independent influence on those related to hypertensive vasculopathy. 11,12 Actually, although we were not able to detect any significant independent contribution of obesity on the risk of deep ICH, we observed a significant IE as a result of the relationships between obesity and its comorbidities. Taken together with previous reports, our data suggest a complex relationship between obesity and cerebral hemorrhage, with different contributions of obesity-related conditions and, indirectly, support the prevailing idea that metabolic factors play a much larger role in the pathogenesis of deep ICH than in cerebral amyloid angiopathy-related hemorrhages.…”
Section: In the Context Of The Current Literaturecontrasting
confidence: 43%
“…In line with this view, 2 recent reports suggested that extreme body mass index (BMI) values might have a differential influence on brain vessels, with a prominent effect on hypertensive deep ICH. 11,12 Second, although there is theoretical support in the literature for the role of specific vascular risk factors as mediators of the effects of obesity on brain hemorrhage, this relationship has yet to be explicitly tested, and relatively little has been published on the explanatory pathways underlying such an eventual relationship.…”
mentioning
confidence: 99%
“…HTN-related ICH is more likely to occur in deep structures[9], and the risk of ICH increases with increasing blood pressure values[10]. CAA tends to occur in association with advanced age, and CAA-related ICH tends to occur in lobar regions.…”
Section: Risk Factorsmentioning
confidence: 99%
“…21 Determining whether risk factors and outcome differ according to ICH location has been further complicated by studies' varied definitions of ICH location. Of 41 observational studies comparing lobar and nonlobar ICH, 20 did not define lobar location, 18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 21 used different definitions of lobar location (including ICH which was cortical, subcortical, or cortical and subcortical, [41][42][43][44][45][46] cerebellar, 47 predominantly cortical and involving underlying white matter, [48][49][50] subcortical or in a hemisphere excluding the basal ganglia or thalamus, [51][52][53] or in any lobe(s) of the brain). [54][55][56][57][58][59][60][61] Of 28 studies that defined nonlobar ICH, 20 defined nonlobar as involving the basal ganglia or infratentorial regions, 18,25,27,<...>…”
mentioning
confidence: 99%